Use of STF in textiles for puncture protection elements - Quiroga Barreto, Angélica Margoth
In the manufacturing and security industry, there is a risk of injuries caused by sharp or pointed objects in sectors such as clothing, metalworking, health, beauty and construction, due to the fact that personnel handle sharp or pointed tools. Police and military officers, as well as correctional officers, are also exposed to stab and sharps injuries; In both cases, this can cause fatal injuries, permanent or temporary disability and trauma that prevent them from performing their duties. For this reason, the use of puncture-resistant personal protection elements is essential to mitigate the risk of occupational accidents.    Throug the use of nanotechnology, it has been possible to functionalize textiles for personal protection elements, giving them exceptional characteristics without affecting their appearance or their mechanical properties. In this study, advances in the use of shear thickening fluids with silica nanoparticles for anti-puncture applications in technical textiles are reported. The influence of different process variables is taken into account to obtain the STF (Shear Thickening Fluid) and the impregnation method in the textile, based on the compilation of different findings in investigations carried out around the world through bibliometric analysis.